Development of Student Evaluation Instruments Using Wordwall Learning Media in Fiqh Lessons Grade 3 Madrasah Diniyah Darut Taqwa - Qur’ana, Wanda Wahyu; Kirom, Askhabul; Mubarok, Achmat; Hadi, Nur (Literacy: Journal of Education and Social Science, 2024)
This research aims to develop an evaluation instrument for student learning through wordwall teaching media in Madrasah Diniyah Darut Taqwa grade 3 fiqh lessons, as well as to determine the effectiveness of wordwall teaching in Madrasah Diniyah Darut Taqwa grade 3 fiqh lessons. This research uses a qualitative approach with the type of Research and Development (R&D), as well as collecting data through observation, interview, and documentation techniques. The results of the study show that the development of learning evacuation instruments through wordwall learning media uses 8 stages out of 10 existing stages, because it is in accordance with the needs of students and the time limitations that researchers have. Wordwall learning media is also still not effective in improving student learning outcomes.